Von Willebrand factor antigen levels predict major adverse cardiovascular events in patients with carotid stenosis of the ICARAS study. (November 2019) - Kovacevic, Katarina D.; Mayer, Florian J.; Jilma, Bernd; Buchtele, Nina; Obermayer, Georg; Binder, Christoph J.; Blann, Andrew D.; Minar, Erich; Schillinger, Martin; Hoke, Matthias
Abstract: Background and aims: Von Willebrand factor (VWF) plays an important role in thrombogenesis and mediates platelet adhesion particularly under high shear stress. Such conditions are generally found in stenotic arteries and can eventually cause myocardial infarction or stroke. We aimed to study whether levels of VWF antigen (VWF:Ag) predict future major adverse cardiovascular events (MACE) in patients suffering from carotid artery stenosis. Methods: Patients with atherosclerotic carotid artery disease defined by the presence of nonstenotic plaques or any degree of carotid stenosis were prospectively enrolled. Concentrations of VWF were measured by enzyme immunoassay. Results: VWF:Ag levels were more stable after 4 freeze-thaw cycles, when compared to VWF activity, and we showed similar concentrations of VWF in citrated plasma and serum (±4%). Levels of VWF:Ag predicted future cardiovascular events in 811 patients with carotid stenosis independent of known cardiovascular risk factors. Patients with VWF:Ag concentrations in the 4th quartile had a 44% event rate after an average 3-year follow up and a hazard ratio of 2.15 (95% confidence interval 1.46–3.16; p < 0.001). Conclusions: High concentrations of VWF:Ag predict major cardiovascular events in patients with carotid stenosis, and given their high event rate may be useful for risk stratification of such patients. Graphical abstract: Image 1 Highlights: The predictive value of VWF for MACE is unknown in patients with asymptomatic carotid stenosis. This large cohort study investigated the predictive value of VWF for MACE in 811 patients with carotid stenosis. VWF levels within the highest quartile were independently associated with a 2.1-fold increase in MACE. This cohort study in 811 patients with carotid stenosis showed that high VWF-levels predicted MACE, which may be useful for risk stratification.